Coherent anti-Stokes Raman scattering microscopy through a multimode fiber endoscope - Tragardh, Johanna; Pikalek, Tomas; Sery, Mojmir; Akimov, Denis; Meyer, Tobias; Popp, Jurgen; Cizmar, Tomas (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Advanced wavefront-shaping methods can be used to transform a simple multimode fiber into an ultra-thin laser scanning microscope. Here, we extend this technique to label-free non-linear microscopy with chemical contrast using coherent anti-Stokes Raman scattering (CARS) through a multimode fiber endoscope, which opens up new avenues for instant and in-situ diagnosis of potentially malignant tissue. We use a commercial, 125 μm diameter, 0.29 NA, GRIN fiber as the endoscopic probe. Wavefront shaping on a spatial light modulator is used to create a focus, where the 1-2 ps long pump and Stokes pulses are overlapped in time, which is scanned behind the fiber facet across the sample. The chemical selectivity is demonstrated by imaging 2 μm polystyrene and 2.5 μm PMMA beads with per pixel integration time as low as 1 ms for epi-detection. Epi-detection through the fiber is possible despite the fact that the CARS signal is emitted mainly in the forward direction, away from the fiber facet. Detecting the back-scattered signal from the underlying tissue, requires a large detector aperture to be efficient. By detecting through both the core and the cladding of the fiber, we obtain sufficient detection efficiency.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Adaptive optics; CARS; Endoscopy; Microscopy; Multi-photon microscopy; Raman